The TNFalpha gene relates to clinical phenotype in alpha-1-antitrypsin deficiency. - Wood, A; Simmonds, M; Bayley, D; Newby, P; Gough, S; Stockley, R (2008)
BACKGROUND: Genetic variation may underlie phenotypic variation in chronic obstructive pulmonary disease (COPD) in subjects with and without alpha 1 antitrypsin deficiency (AATD). Genotype specific sub-phenotypes are likely and may underlie the poor replication of previous genetic studies. This study investigated subjects with AATD to determine the relationship between specific phenotypes and TNFalpha polymorphisms. METHODS: 424 unrelated subjects of the PiZZ genotype were assessed for history of chronic bronchitis, impairment of lung function and radiological presence of emphysema and bronchiectasis. A subset of subjects with 3 years consecutive lung function data was assessed for decline of lung function. Four single nucleotide polymorphisms (SNPs) tagging TNFalpha were genotyped using TaqMan(R) genotyping technologies and compared between subjects affected by each phenotype and those unaffected. Plasma TNFalpha levels were measured in all PiZZ subjects. RESULTS: All SNPs were in Hardy-Weinberg equilibrium. A significant difference in rs361525 genotype (p = 0.01) and allele (p = 0.01) frequency was seen between subjects with and without chronic bronchitis, independent of the presence of other phenotypes. TNFalpha plasma level showed no phenotypic or genotypic associations. CONCLUSION: Variation in TNFalpha is associated with chronic bronchitis in AATD.